DAMPAK PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN TERHADAP PENDAPATAN PETANI ANGGOTA GAPOKTAN DI KECAMATAN PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Jojor Marety; Cepriadi '; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is to find out the impact of Rural Agribussines Development Program (PUAP) towards the member of Gapoktan farmer income as donation assist receiver and identify the problem which appear from usage of donation program in Pagaran Tapah Darussalam District. Sample is take by using purposive sampling method among 28 respondent. Data analysis used t-test pair analyst. Based on the result of this research, the member of Gapoktan farmer income have been growth amount 32,56%, which the average of palm oil farmer income before gettig assist of PUAP amount Rp. 26.956.846,- and after getting assist of PUAP has been increased become Rp. 35.733.200. this analyst is taken by t test pair analyst and find the result that volume of t is bigger than t table (7,824 > 2,052) it means that  H0 accepted and H1 is rejected. PUAP program also give real effect toward farmer respondent income that has been seen from value significant which obtained more little from significant coefficient (0,00 < 0,01). After using PUAP program, almost all the problem that the farmer faced are about time and amount of realisasi loan donation (68,86%) which received by member o farmers did not exist with the farmer ask, it also about acces or method in doing donation loan PUAP (57,14%), where the farmer have to make RUA (Bussines Plan Member) firstly. Keywords : Impact, Farmer Income, PUAP